If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7(x + -8) = 48 Reorder the terms: 5x + -7(-8 + x) = 48 5x + (-8 * -7 + x * -7) = 48 5x + (56 + -7x) = 48 Reorder the terms: 56 + 5x + -7x = 48 Combine like terms: 5x + -7x = -2x 56 + -2x = 48 Solving 56 + -2x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + -2x = 48 + -56 Combine like terms: 56 + -56 = 0 0 + -2x = 48 + -56 -2x = 48 + -56 Combine like terms: 48 + -56 = -8 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
| c=2.02w+15.83 | | 18(n+1)= | | (9x^3-4x^2-7)+(-2x^3-2x-4)=0 | | a^2+1=25 | | =5x^2-8x-4 | | =27x^2-90x+27 | | 9x^2+12x+4=12 | | (n+9)+1= | | =3x^2-x-2 | | x(-3x+7)=21 | | 5y+-3x=5 | | -x^2+4=9x+1 | | 7(x+4)= | | 9x+6=16x+8 | | 15-x=11 | | 12v^2=27 | | 2x-(x+12)=3x-10 | | 3x+9=6x+36 | | x-7=-8-2x | | 3(c+5)=8c-20 | | 6w+3=6.2+w | | 700-65= | | 6w+3=6*2+w | | 5x^2=24x+36 | | 8x+2=4x+26 | | -(8y+3)-(-7-8)=4 | | 65-32= | | x-40=5 | | Bc+ac=ab | | x-40= | | 11x-19=113 | | x(5x+10)=2x^2-13x+8 |